(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2017)
While the majority of scholars hold that in classical Athens there was a statute establishing that all agreements (homologiai) were valid, some have questioned this view. The most commonly used argument for the existence of a specific law on agreements is the presence of a few passages in the Attic orators where reference is allegedly made to such a statute. The present article argues that these passages do not actually settle the question. The Attic orators usually only cite single paragraphs out of longer legal texts – notwithstanding their frequent use of the word nomos to refer to the passages they cite – and give us no clue as to their position and function in the con- text of the statute, which becomes clear if we compare the extant inscription of Draco’s law on homicide with its citations in the orators. It is thus impossible to settle the question of whether a single and specific law on agreements existed based on citations found in forensic speeches. All we can do is make a probability assessment based on what is otherwise known about homologia clauses in Greek law.